2018
DOI: 10.1039/c8cp00503f
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene size controls the selective complexation of [11]CPP with pristine and endohedral fullerenes

Abstract: The ability of the carbon nanoring [11]cycloparaphenylene ([11]CPP) for coordinating fullerenes has been tested using a series of hosts, including the pristine fullerenes C60, C70, C76 and C78, the clusterfullerene Sc3N@C80, monometallic endofullerenes Y@C82 and Tm@C82, and dimetallic endofullerenes Y2@C82 and Lu2@C82. A systematic theoretical study employing dispersion corrected density functional methods has been carried out in order to explore the characteristics of the complexes and the strength of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 96 publications
1
30
0
Order By: Relevance
“…For further discussion, see Figures S12 and S13 and the respective text in the SI. Figure 11a shows an example of reversible shape deformation of [10]CPP through ovalization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For further discussion, see Figures S12 and S13 and the respective text in the SI. Figure 11a shows an example of reversible shape deformation of [10]CPP through ovalization.…”
Section: Resultsmentioning
confidence: 99%
“…The unusual cyclic molecular symmetry of [n]CPPs offers a unique case of cyclic circulation of the −electron density, or cyclic −conjugation, which confers on them distinct optical and electronic properties governed by their increasing strain with decreasing n. 9 The −conjugated scientific community has been captivated by the circular aromaticity of [n]CPPs, their tunable size, varying degrees of aromaticity, unique sizedependent supramolecular properties, encapsulation of guest molecules and promising applications in material science. 10,11 Because [n]CPPs represent the shortest segments of armchair single wall carbon nanotubes (SWCNTs) 12 , they can also serve as model systems not only to conceive the bottomup synthesis of SWCNTs but also to elucidate the nature of the interaction of the nanotube host with guests, as well as other interesting properties. 13,14,15 Since the first synthesis of [n]CPPs (n=9, 12, and 18) in 2008, 16 the family of [n]CPPs was quickly expanded to include the n=5- 16, and 18 members of the series and diversified into other functionalized derivatives using various synthetic methods.…”
Section: Take Down Policymentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual cyclic molecular symmetry of [n]CPPs offers a unique case of cyclic circulation of the π-electron density, or cyclic π-conjugation [13,18,19], which confers on them distinct optical and electronic properties governed by their increasing strain with decreasing n [20,21]. The versatility of these systems in terms of aromaticity, unique size-dependent supramolecular properties and encapsulation of guest molecules leads to promising applications in materials science [22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yamago's group reported that C 60 can be selectively encapsulated by [10]CPP and detected the host‐guest interaction by 1 H‐NMR spectroscopy . A very recent report by González‐Veloso et al showed that [11]CPP could be capable of separating the fullerenes larger than C 76 from a mixture also containing C 60 and C 70 . The encapsulation by CPPs may not only lead to new functional materials, but also can be used for selective extraction of a given fullerene from mixture.…”
Section: Introductionmentioning
confidence: 99%